Studi Kasus di Rumah Sakit Tipe C dan Tipe B: Analisis Identifikasi dan Autentikasi Dokumen Rekam Medis Berbasis SNARS - Eni Mahawati; Elyta Oviana; Nela Indah Suryan; Lulu Maftukhatul Khasanah (Dian Nuswantoro Semarang, 2019)
Implementation of patient identification based on SNARS can support patient safety programs. Based on the initial survey of medical record quantitative analysis of 20 inpatient medical record documents have known that were 30% incomplete identification, 40% incomplete reporting, 50% were incomplete recording and 30% incomplete authentication. The purpose study was to analyze identification and authentication incomplete medical records based on SNARS to support patient safety program. It was a descriptive study with observational collecting data method of 225 medical record documents. The results of the study identify 58.30% incomplete identification of medical record in type C hospital and 14,38% in type B hospital. Other results show there were 66.67% incomplete authentication (incomplete signature) of medical records in type C hospital and 45.75 % in type B hospital. There was 65.3% incomplete officer name of medical records in type C hospital and 9.15 % in type B hospital. Incomplete writing place, date and time of medical records 70.8% in type C hospital and 16.34 % in type B hospital. It was concluded that were significant differences in medical records incomplete based on identification and authentication in type B and C hospital. Suggestions, to handle the incompleteness of medical record documents, regular meetings with all PPAs need to be held to evaluate the staff performance and increase staff awareness in completing medical record documents to support quantitative analysis medical records, especially based on SNARS standard accreditation. Keywords: SNARS, Identification, authenthicationLiterature: 9 (2008-2018)